Development and Implementation of Integrated Science Learning Learning Devices for 2013 Curriculum Susan Loucks-Horsley Model - Zulhelmi, Zulhelmi; Arnentis, Arnentis; Rasmiwetti, Rasmiwetti (Proceedings of the UR International Conference on Educational Sciences, 2018)
This study aims to develop a model learning tool for Susan Loucks-Horsley that is suitable to be used for Integrated science learning in junior high school grade VII semester 1, investigating the validity, practicality and effectiveness of learning tools in improving student learning outcomes of science materials. Research uses the method of Development Research four D models (definition, design, development, desimination). Learning tools developed in the form of Learning Implementation Plans, Student Learner Worksheets and Assessment Sheets.Data collection uses a validation sheet for learning tools for assessment of Learning Plans,Student Worksheets and Sheets Assessment., Assessment Sheet by experts and users; questionnaire to find out the practicality; observation sheets to observe student activities, and test learning outcomes to determine the effectiveness of the device. Data analysis was performed with quantitative descriptive techniques and different tests. The research was carried out only until the definition stage and design development of the Model Susan Loucks-Horsley learning tool in VII grade junior high school science in energy systems in living systems